Development of Theological-Apologetical Discourse in Biblical Studies at Kiev Theological Academy of the late XIX - early XX centuries - Sergii HOLOVASCHENKO (Богословські роздуми: Східноєвропейський журнал богословʼя)
The article highlights the development of hermeneutical strategies for the analysis and refutation of rationalist “negative” biblical criticism, represented by the works of leading theologians - professors of the Kiev Theological Academy of the late XIX - early XX centuries. In the conditions of secularization, the decline of church authority, the spread of political radicalism, the need for apologetic understanding of the biblical heritage increased. A systematic analysis of the signs, approaches and methods of rationalism in biblical studies has been heuristicly valuable, in particular: criticism of panlogism, abstract schematics, empirically groundless extrapolations and generalizations. At the same time, Kyiv Biblical scholars criticized the insolvent apologetic techniques: the literalistic view of the inspiration, the absolute authority of the tradition, the excessive spiritualization in the perception of the biblical prophecy. Their main goal was to prove the authenticity and authenticity of the content of biblical books and the very biblical hystory. The methodological impulse for the biblical apologetics was the intensification of supranaturalism, providentialism, and soteriology in the reading and interpretation of the Bible - just as the Holy Scriptures of the Church. The apologetic motive was to determine both scientific bibliological studies, and school teaching and study of the Bible, and private and public Biblical reading for religious and moral instruction.